A Systematic Review and Meta-analysis Comparing Clinical Outcomes After Concurrent Rotator Cuff Repair and Long Head Biceps Tenodesis or Tenotomy. (July 2015) - Leroux, Timothy; Chahal, Jaskarndip; Wasserstein, David; Verma, Nikhil N.; Romeo, Anthony A.
Context: A comparison of clinical outcomes after long head of biceps (LHB) tenotomy or tenodesis performed concurrently with rotator cuff repair (RCR) is of interest to physicians and patients. Objective: A systematic review of clinical outcome studies examining LHB tenotomy or tenodesis performed concurrently with RCR. Secondarily, perform a meta-analysis of data from comparative studies. Data Sources: MEDLINE (1946 to week 30 of 2013) and EMBASE (1980 to week 30 of 2013). Study Selection: Levels 1 through 4 studies reporting clinical outcomes of concurrent RCR and LHB tenotomy or tenodesis with minimum 1-year follow-up. Study Design: Systematic review and meta-analysis. Level of Evidence: Level 4. Data Extraction: Two independent reviewers identified eligible studies and applied the exclusion criteria. Clinical outcome data, including functional outcome score(s), biceps deformity and cramping, and patient satisfaction, were extracted. Clinical outcome data from included studies were pooled (weighted according to study size) and reported. A meta-analysis was performed only on outcomes extracted from comparative studies (α = 0.05). Results: Twelve studies (N = 565 patients; mean age, 61.3 years; 46.3% men) were included. Of these, 6 (N = 263) included RCR and LHB tenotomy and 9 (N = 302) included RCR and LHB tenodesis. A meta-analysis was performed on 3 comparative studies (levels 1 and 2), demonstrating that the postoperative Constant score at a mean follow-up of 25.5 months was significantly greater after tenodesis (92.8 [tenodesis] vs 90.6 [tenotomy], P < 0.01); however, this difference was less than the reported minimal clinically important difference of 10.4 points. Similarly, the rate of biceps deformity was significantly less after tenodesis (15.5% [tenotomy] vs 3.9% [tenodesis], P < 0.01); however, most patients were not bothered by it. There were no significant differences in the rate of biceps cramping or patient satisfaction. Conclusion: Although the postoperative Constant score and rate of biceps deformity favor LHB tenodesis statistically, the clinical significance appears negligible.